Estudo dos óbitos maternos na região metropolitana de Belém - CAMACHO, Elyade Nelly Pires Rocha (Universidade Federal do Pará, 2023)
Data on maternal mortality, whether in developed or developing countries, are more disparate than any other indicator of public health in Brazil. During the United Nations Millennium Development Pact, eight Development Goals were adopted, among them, to reduce maternal mortality by 75% by 2015. The aim of the study was to conduct a study on the occurrence of maternal deaths in the region Metropolitan area of Belém that were notified through the Mortality Information System (MIS) from January 2013 to December 2015, in addition to describing the main causes of maternal mortality. The study is an epidemiological, descriptive, quantitative, analytical, retrospective and documentary approach. It is performed with secondary data stored at the Maternal Mortality Committee consisting of results reported as maternal deaths. From January 2013 to December 2015, 53 deaths were reported in 2013, 45 maternal deaths in 2014 and 40 deaths in 2015. The data identified a maternal mortality ratio (MMR) of 160.3 deaths per 100 A thousand live births in 2013, 136.0 deaths per 100,000 live births in 2014 and 121.9 deaths per 100,000 live births in 2015. We can say that the epidemiological profile is not well defined, diverging with several Literatures. The main causes of maternal mortality are in the world, in Brazil and especially in the metropolitan region I of the state of Pará, the four apocalyptic horsemen, who kill women, Hypertensive Syndrome, Hemorrhage, Sepsis and Abortion remain. That is, despite all the discussions on the subject, the RMM does not diminish over the years, reinforcing the need for improvements in the state's public health.